2008
DOI: 10.1007/s00276-008-0309-6
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the intracranial vertebrobasilar system

Abstract: Our results show that a high percentage of variations can be seen even in a small number of cases. We believe that our data are clinically important because, for example, variations are a factor which increases the incidence of aneurism and thrombus. We also think our results will contribute to the demography of our country and to clinical medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
5
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 16 publications
8
51
5
2
Order By: Relevance
“…Left dominancy was observed in 21.2% and right dominancy was observed in 17.3% [14]. With this criterion, in our study right VA was found to be dominant in 20.1% of the patients and left VA was found to be dominant in 17.3% of the patients.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Left dominancy was observed in 21.2% and right dominancy was observed in 17.3% [14]. With this criterion, in our study right VA was found to be dominant in 20.1% of the patients and left VA was found to be dominant in 17.3% of the patients.…”
Section: Discussionsupporting
confidence: 62%
“…In the literature vertebral arteries are investigated by colour Doppler ultrasound, anatomic studies, computed tomography angiography (CTA) and conventional angiography in many years [10,11,[14][15][16]. B-mode and colour Doppler ultrasound is the first--step method in evaluation of vertebrobasilar system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was 25.3% in a study conducted by Padmavathi [10].Songur et al [11] recorded According to Mccullough,the triplication rate was 3%.It was 2% as reported by Mani et al and Padmavathi. In the current study, it was 2.5%.…”
Section: Resultsmentioning
confidence: 82%
“…The SCA-PCA common trunk may compress the oculomotor nerve as it lies in the crux between SCA and PCA and may cause its palsy. Duplication is the most common anomaly described in the literature with a frequency of 11% to 36%.Duplication was reported by Mccullough [12], Hardy et al [9],Songur et al [11],Pai BS et al [8],and Julius Ogeng'o et al [7].It was also reported by Mani et al [13],and Uchino et al [1] by analysing the angiographic pictures. Padmavathi [10] studied the variations of SCA and reported the duplication rate as 23.3%.…”
Section: Resultsmentioning
confidence: 96%